Income inequality and economic growth: A re-examination of theory and evidence - Balcilar, Mehmet; Gupta, Rangan; Ma, Wei; Makena, Philton (Wiley, 2021)
We re-examine the theoretical and empirical relationship between income inequality and long-run economic growth in an endogenous growth model with a flat tax on income, distributive conflicts among agents, and median voter dynamics. We show that when government spends tax revenue on the provision of public goods in the form of both production and consumption services, the theoretical relationship between inequality and economic growth is neither strictly positive nor strictly negative, but ambiguous. An empirical evaluation of the theoretical findings is carried out by applying a semi-parametric model on a sample of 63 countries for the period 1991-2017. Results show that the relationship between income inequality and growth takes the form of an inverted U-shape in that income inequality initially has a positive impact on growth up to an average Gini coefficient threshold of 35.92, beyond which it negatively impacts on growth.
Keywords: Inequality; economic growth; endogenous growth; semi? parametric model